Variations of Gut Microbiome Profile Under Different Storage Conditions and Preservation Periods: A Multi-Dimensional Evaluation - Ma, Junli; Sheng, Lili; Hong, Ying; Xi, Chuchu; Gu, Yu; Zheng, Ningning; Li, Mengci; Chen, Linlin; Wu, Gaosong; Li, Yue; Yan, Juan; Han, Ruiting; et al. (Frontiers in Microbiology, 2020)
Gut dysbiosis is heavily involved in the development of various human diseases. There are thousands of publications per year for investigating the role of gut microbiota in diseases. However, emerging evidence has indicated the frequent data inconsistency between different studies, which is largely over looked. There are many factors that can cause data variation and inconsistency during the process of microbiota study, in particular, sample storage conditions and sequencing process. Here, we systemically evaluated the impacts of six fecal sample storage conditions (three non-commercial storage protocols, -80 ℃, -80 ℃ with 70% ethanol (ET_-80 ℃), 4°C with 70% ethanol (ET_4℃), and three commercial storage reagents, OMNIgene•GUT OMR-200 (GT) and MGIEasy (MGIE) at room temperature, and Longsee at 4℃(LS) on gut microbiome profile based on 16S rRNA gene sequencing. In addition, we also investigated the impacts of storage periods (1, 2 weeks or 6 months) and sequencing platform on microbiome profile. The efficacy of storage conditions was evaluated by DNA yield and quality, α and β diversity, relative abundance of the dominant and functional bacteria associated with short-chain fatty acid (SCFA) production and BAs metabolism. Our current study suggested that -80℃ was acceptable for fecal sample storage, and the addition of 70% ethanol had some benefits in maintaining the microbial community structure. Meanwhile, we found that samples in ET_4 ℃and GT reagents were comparable, both of them introduced some biases in α or β diversity, and the relative abundance of functional bacteria. Samples stored in MGIE reagent resulted in the least variation, whereas the most obvious variations were introduced by LS reagents. In addition, our results indicated that variations caused by storage condition were larger than that of storage time and sequencing platform. Collectively, our study provided a multi-dimensional evaluation on the impacts of storage conditions, storage time periods, and sequencing platform on gut microbial profile.